A Humanized Monoclonal Antibody Cocktail to Prevent Pulmonary Ricin Intoxication - Yinghui Rong; Michael Pauly; Adrian Guthals; Henry Pham; Dylan Ehrbar; Larry Zeitlin; Nicholas J. Mantis (Toxins, 2020)
PB10 IgG1, a monoclonal antibody (MAb) directed against an immunodominant epitope on the enzymatic subunit (RTA) of ricin toxin (RT), has been shown to passively protect mice and non-human primates from an aerosolized lethal-dose RT challenge. However, it was recently demonstrated that the therapeutic efficacy of PB10 IgG1 is significantly improved when co-administered with a second MAb, SylH3, targeting RT’s binding subunit (RTB). Here we report that the PB10/SylH3 cocktail is also superior to PB10 alone when used as a pre-exposure prophylactic (PrEP) in a mouse model of intranasal RT challenge. The benefit of the PB10/SylH3 cocktail prompted us to engineer a humanized IgG1 version of SylH3 (huSylH3). The huPB10/huSylH3 cocktail proved highly efficacious in the mouse model, thereby opening the door to future testing in non-human primates.